Role of hematological and immunological parameters in COVID-19 patients - Avanindra Kumar; Shipra Sepolia; R H Shilpa; Gilda Rezayani; Soni Kumari; Aastha; Shivangi Gupta (Wolters Kluwer Medknow Publications, 2021)
Background: The ongoing pandemic of coronavirus disease 2019 (COVID-19) which was caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to efforts from the medical and scientific community in understanding the biological basis of COVID-19 pathophysiological mechanisms. Thus, analysis of various hematological and immunological parameters may be helpful for COVID-19 infection evaluation for risks involved and effectiveness in management. Aim: The aim of this study was to analyze the role of various hematological and immunological parameters in patients infected with SARS-CoV-2. Materials and Methods: This retrospective analysis was performed on 300 patients who tested positive for SARS-CoV-2 by quantitative reverse transcription-polymerase chain reaction analysis. All participants of the study were divided into - (a) Group I: patients with mild symptoms and normal chest radiographic findings; (b) patients with moderate disease presenting with fever and cough along with other respiratory symptoms, and (c) patients suffering from severe disease. Data collection was done from all patients at the time of hospital admission for hematological and immunological parameters - (a) total leukocyte count, (b) lymphocyte count, (c) lymphocytic subset count, (d) lactate dehydrogenase (LDH) levels, (e) D-dimer, (f) C-reactive protein (CRP), and (g) ferritin levels. SPSS 22.0 software was used for determining P values by independent t-test and Chi-square test. Results: The median age was 65 years (interquartile range -57-71 years). While comparing white blood cell and lymphocyte counts, extremely significant P values were obtained. D-dimers and ferritin levels demonstrated extremely significant P values while both LDH and CRPs showed statistical significance. Correlation of lymphocytic subsets showed extreme significance in total lymphocyte counts in mild-to-moderate as compared to severely infected patients while both CD4+ and CD8+ counts demonstrated statistical significance in mild-moderate infected cases. Statistical significance was noted in D-dimer, CRP, and LDH levels also. Conclusion: Assessment of hematological and immunological parameters can be used to plan the management of COVID-19 patients.